Synergistic Undernutrition: The Metabolic Nexus Between Chronic Energy Deficiency and Anemia in Rural Balinese Pregnant Women - I Putu Adigama; I Nyoman Sayang; Gusti Ngurah Nyoman Yuliastina; I Made Pasek Soma Gauthama (Community Medicine and Education Journal, 2025)
Despite the widespread implementation of Iron-Folic Acid (IFA) supplementation programs, the prevalence of maternal anemia in Indonesia remains stagnant, suggesting a multifactorial etiology beyond simple micronutrient deficiency. In rural agrarian settings, macronutrient adequacy—specifically protein-energy balance—may play a critical, yet overlooked, role in hematopoiesis. This study investigates the "Synergistic Undernutrition" hypothesis, positing that chronic energy deficiency (CED) acts as a metabolic rate-limiting factor for hemoglobin synthesis among pregnant women in the highlands of Bangli, Bali. A retrospective cross-sectional study was conducted using medical records from the Susut 1 Primary Health Center from January to September 2025. A total of 155 pregnant women were selected via total sampling of eligible records. Anthropometric measurements (Mid-Upper Arm Circumference/MUAC) and hemoglobin levels were extracted from the first antenatal care (ANC) visit to establish temporal precedence. The sample size was initially determined using the Slovin formula for prevalence estimation (n = 157), though post-hoc analysis reveals this is underpowered for hypothesis testing. Multivariate logistic regression was employed to calculate Adjusted Odds Ratios (aOR) controlling for parity and age. The prevalence of CED (MUAC <23.5 cm) was 37.4%, and anemia (Hb <11 g/dL) was 41.9%. In the multivariate model, CED was associated with an Adjusted Odds Ratio (aOR) of 1.88 (95% CI: 0.97–3.67). While the p-value (0.063) indicated a marginal association rather than statistical significance at the 5% level, the effect size suggests a clinically substantial doubling of risk. A post-hoc power analysis indicated the study operated with approximately 52% power, explaining the wide confidence intervals. Multiparity also showed a similar marginal association (aOR 1.88; p=0.066). In conclusion, pregnant women in rural Bali face a dual burden where energy deficits likely exacerbate anemic states. Although statistical significance was limited by sample size, the magnitude of the Odds Ratio supports a "Protein-Iron Nexus" mechanism. Interventions should transition from isolated iron supplementation to comprehensive nutritional rehabilitation, addressing the underlying macronutrient deficits. Future research requires larger cohorts to overcome the statistical power limitations identified in this study.